Perspective on Predominant Metal Oxide Charge Transporting Materials for High-Performance Perovskite Solar Cells - Singh, Mriganka; Chu, Chih Wei; Ng, Annie (Frontiers in Materials, 2021)
The power conversion efficiency of organometallic mixed halide perovskite solar cells (PSCs) is beyond 25%. To fabricate highly efficient and stable PSCs, the performance of metal oxide charge transport layers (CTLs) is one of the key factors. The CTLs are employed in PSCs to separate the electrons and holes generated in the perovskite active layer, suppressing the charge recombination rate so that the charge collection efficiency can be increased at their respective electrodes. In general, engineering of electron transport layers (ETLs) are found to be dominated in research community to boost the performance of PSCs due to the resilient features of ETLs such as excellent electronic properties, high resistance to thermal temperature and moisture, ensuring good device stability as well as their high versatility in material preparation. The hole transport layers (HTLs) in PSCs are recently intensively studied. The performance of PSCs is found to be very promising by using optimized hole transport materials (HTMs). This review concisely discusses the evolution of some prevalent metal oxide charge transport materials (CTMs) including TiO2, SnO2 and NiOX, which are able to yield high performance PSCs. The article begins with introducing the development trend of PSCs using different types of CTLs, pointing out the important criteria for metal oxides being effective CTLs and then a variety of preparation methods for CTLs as employed by the community for high performance PSCs are discussed. Finally, the challenges and prospective for the future research direction towards scalable metal oxide CTMs based PSCs are delineated.